Life sciences - Sorman, Joy, 1973- (Restless Books, 2021)
For centuries, the women in Ninon Moise's family have been afflicted by obscure, inexplicable medical phenomena. Seventeen-year-old Ninon is no exception to this bizarre family inheritance, and she wakes one morning with a debilitating and excruciatingly painful response to touch on her arms. Unlike her forebears, Ninon refuses to passively accept her cursed fate and rebels against the indifferent medical professionals who dismiss her condition as uninteresting, feminine, obscure, niche, or incurable. A taut, daring parable of womanhood, Life Sciences is a bold reclamation of self and bodily autonomy as Ninon struggles to define her own destiny.